The Study of Three-dimensional Image of the Structure in 7 and 9 Days Old Chick Embryos from Micro-computed Tomography (Micro-CT) - Rumpansuwan, Kanitin; Boonnoon, Nutdanai (Journal of Mahanakorn Veterinary Medicine, 2022)
Currently, the study of organ development in organisms uses both serial sections and whole-mount under microscope examination. Despite the fact that these developmental processes are well defined, the dimension often overlooked in order to obtain the most precise images. Thus, 3D reconstruction and morphometry are applied for illustrating of the embryonic development. In this study, the micro-computed tomography (micro-CT) was applied and analyzed morphometrically and volumetrically in Amira 3D software. The 3D model from the reconstruction showed the structure of the embryo as well as the volume of chick embryos without causing any damage to the samples. It was also possible to automatically display sectioning in different planes, allowing for the analysis of multiple planes of chick embryos, as compared to mechanically serial section-based three dimensional reconstruction, which was only capable of displaying sectioning in particular plane. However, in order to generate a three-dimensional image that clearly distinguishes tissue from micro-computed tomography (micro-CT) analysis, it is necessary to add a step of enhancing the color contrast of the image before it is placed into the micro-computed tomography (micro-CT). Thus, this study of 3D image of the structure of chick embryos from Micro-computed tomography (micro-CT) can be used to demonstrate morphological changes in embryonic development.